Comparative fatigue analysis of wrought and laser powder bed fused Ti-6Al-4V for aerospace repairs: academic and industrial insights - Nagalingam, Arun Prasanth (2023)
Additive manufacturing (AM) holds great promise for delivering benefits in repair of aerospace components. To fully exploit the benefits of AM, it is crucial to demonstrate that AM-produced components satisfy the performance criteria specified by the aerospace industry relative to conventional wrought material. This research assesses the performance of laser-powder bed fused (L-PBF) and wrought Ti-6Al-4V coupons following the aerospace method of manufacture (MoM), which ensures that the material undergoes both surface and sub-surface enhancement to meet fatigue requirements. The results reveal that the aerospace MoM-treated L-PBF Ti-6Al-4V coupons exhibit superior fatigue life compared to their wrought counterparts. Furthermore, it is understood that the vibratory polishing process retains the beneficial compressive residual stress from shot peening, while simultaneously enhancing the surface finish and fatigue life. Finally, a life-cycle cost model assessment highlights that the L-PBF coupons have superior fatigue life and are cost-effective particularly for low-volume repairs, while the use of wrought material is economical for large-volume repair but may compromise fatigue life.